The paradox of formalization and informalization in South-North value chains - Dannenberg, Peter; Braun, Boris; Kulke, Elmar (DIE ERDE – Journal of the Geographical Society of Berlin, 2016)
The internationalization of value chains and the broad proliferation of different public and private standards have led to a formalization and standardization of value chains, production systems and their constitutional actors and linkages in the Global South. Recent studies on the integration of Southern production systems in international value chains, however, show that this is only partly the case. These studies identify limits and insufficiencies of formal and standardized coordination and control systems as well as a neglect of regional peculiarities, individual aims and capabilities of the embedded stakeholders in the South by the coordinating lead firms from the North. As a result, informal actors and arrangements continue to be, and even continue to develop as, important parts of Southern production systems. With reference to the concept of informality, principal-agent theory and convention theory, this study aims to contribute to the recent conceptual debate on global value chains and global production networks in outlining the importance of informal arrangements and non-industrial conventions as well as the limits to upgrading in South-North relationships. The empirical base are case studies on export-oriented primary production systems in Kenya (horticulture), Bangladesh (shrimps) and India/Bangladesh (leather).